Development of Centrifugation Tool to Improve Laboratory Performance and Problem Solving Skills - Pratiwi, Roza Citra; Fadiawati, Noor; Diawati, Chansyanah (FKIP Universitas Lampung, 2022)
This study aims to develop centrifugation tool to improve performance in the laboratory and problem solving skills. The research method used is Research and Development (R&D) with 4D model. The results showed that the developed centrifuge was declared according to the material, had educational value, was durable, precise in measurement, efficient and safe for students based on the responses of teachers and students respectively at 100% and 96.15% with very high criteria. Student performance scores in the laboratory have a distribution close to the average student performance score (91.52). The effectiveness of the application of centrifugation using the students’ worksheet obtained good results in improving problem solving skills with moderate criteria (0.60) and giving moderate effect (0.42). Based on these results, the developed centrifuge was declared effective for improving laboratory performance and problem solving skills. Keywords: centrifuge, student performance, problem solving. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp853-865